2021
DOI: 10.1093/europace/euab275
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance determinants of ventricular arrhythmic events after myocardial infarction

Abstract: Aims To non-invasively characterize, by means of late gadolinium enhancement cardiac magnetic resonance (LGE-CMR), scar differences, and potential variables associated with ventricular tachycardia (VT) occurrence in chronic post-myocardial infarction (MI) patients. Methods and results A case–control study was designed through retrospective LGE-CMR data analysis of chronic post-MI patients (i) consecutively referred for VT sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Acosta et al 24 found the presence, extension, heterogeneity, and qualitative distribution of BZ tissue of myocardial scar to independently predict appropriate ICD therapies and SCD. Similarly, Jáuregui et al 25 demonstrated that the BZ channels mass was the strongest independent variable associated with the occurrence of VT in post-MI patients. Results are comparable to the current.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Acosta et al 24 found the presence, extension, heterogeneity, and qualitative distribution of BZ tissue of myocardial scar to independently predict appropriate ICD therapies and SCD. Similarly, Jáuregui et al 25 demonstrated that the BZ channels mass was the strongest independent variable associated with the occurrence of VT in post-MI patients. Results are comparable to the current.…”
Section: Discussionmentioning
confidence: 82%
“…However, to our knowledge, this has not been demonstrated in earlier studies using the same method as ours. 5 , 14 , 15 , 21 , 24 , 25 Also, our study population was small and might not reach statistical significance due to lack of power.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, patients who have suffered a myocardial infarction are more likely to develop chronic ischemic heart failure [21], which increases the chance of CV death. In addition, due to myocardial ischemia and vagal stimulation, arrhythmias such as sinus bradycardia and atrioventricular block are prone to occur in the early stages of myocardial infarction [22,23]. Some common risk factors, such as blood glucose, blood lipids, and blood pressure, can also cause new CV events in individuals who have already had a heart attack or stroke [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of channels and the border zone channel mass has been shown to be the strongest determinant of VA occurrence after a myocardial infarction after adjustment for other variables related with the LV function and scar. 114 These channels also distinguish patients at higher risk of VTs during follow-up in other clinical situations like cardiac resynchronization therapy and even in non-ischaemic cardiomyopathy. 109 , 111 , 115 …”
Section: Cardiac Imaging For Ventricular Arrhythmias Proceduresmentioning
confidence: 99%